Nutrition, Vitamin D, and Calcium in Elderly Patients before and after a Hip Fracture and Their Impact on the Musculoskeletal System: A Narrative Review - Cianferotti, Luisella; Bifolco, Giuseppe; Caffarelli, Carla; Mazziotti, Gherardo; Migliaccio, Silvia; Napoli, Nicola; Ruggiero, Carmelinda; Cipriani, Cristiana (Nutrients, 2024)
Hip fractures are a major health issue considerably impacting patients’ quality of life and well-being. This is particularly evident in elderly subjects, in which the decline in bone and muscle mass coexists and predisposes individuals to fall and fracture. Among interventions to be implemented in hip fractured patients, the assessment and management of nutritional status is pivotal, particularly in subjects older than 65. Nutrition plays a central role in both primary and secondary preventions of fracture. An adequate protein intake improves muscle mass and strength and the intestinal absorption of calcium. Other nutrients with recognized beneficial effects on bone health are calcium, vitamins D, K, and C, potassium, magnesium, folate, and carotenoids. With reference to calcium, results from longitudinal studies showed that the consumption of dairy foods has a protective role against fractures. Moreover, the most recent systematic reviews and meta-analyses and one umbrella review demonstrated that the combination of calcium and vitamin D supplementation significantly reduces hip fracture risk, with presumed higher efficacy in older and institutionalized subjects. Owing to these reasons, the adequate intake of calcium, vitamin D, protein, and other macro and micronutrients has been successfully implemented in the Fracture Liaison Services (FLSs) that represent the most reliable model of management for hip fracture patients. In this narrative review, papers (randomized controlled trials, prospective and intervention studies, and systematic reviews) retrieved by records from three different databases (PubMed, Embase, and Medline) have been analyzed, and the available information on the screening, assessment, and management of nutritional and vitamin D status and calcium intake in patients with hip fractures is presented along with specific prevention and treatment measures.